Corporate Governance, Profitability, Media Exposure, and Firm Value: the Mediation Role of Environmental Disclosure - Kurniansyah, Firdaus; Saraswati, Erwin; Rahman, Aulia Fuad (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
This study aims to examine and analyze environmental disclosure's effect in mediating the relationship between corporate governance, profitability, and media exposure towards firm value. Total 135 samples of companies that have been listed on IDX in 2015 - 2019 were obtained and analyzed using multiple linear regression. This study showed that corporate governance and profitability increase firm value as investors tend to see corporate governance and profitability as a signal in determining investing decisions. Meanwhile, media exposure and environmental disclosure cannot increase firm value. This study also finds that corporate governance decreases ecological disclosure. Meanwhile, profitability and media exposure cannot increase firm value. Thus, this study also proves that corporate governance, profitability, and media exposure cannot increase firm value through environmental disclosure.